*Relationship Between Creativity and Intelligence: A Multimethod Investigation of Alternative Theoretical Assumptions in Two Samples of Secondary School Students. (April 2023) - Breit, Moritz; Preuß, Julian; Scherrer, Vsevolod; Moors, Tobias; Preckel, Franzis
The threshold hypothesis and the necessary-but-not-sufficient hypothesis represent popular views on the relationship between intelligence and creativity. However, most studies investigating these hypotheses used suboptimal or even inappropriate statistical methods, calling into question the robustness of the available evidence. The ability differentiation hypothesis presents a third theoretical view on the relationship, but ability differentiation studies including creativity measures are scarce. In this study, the relationship between fluid intelligence as a core element of intelligence and divergent thinking as an important indicator of creativity was investigated in two large samples of secondary school students in Germany ( N = 1, 328, M age = 14.47; N = 524, M age = 13.77). Four different statistical approaches were applied (i.e., test for heteroscedasticity, segmented regression analysis, local structural equation modeling, and necessary-but-not-sufficient condition analysis). The results did not support the threshold hypothesis or a nonlinear relationship as predicted by ability differentiation hypothesis and only partially supported the necessary-but-not-sufficient hypothesis.